RESTORASI IMAGO DEI SEBAGAI LANDASAN KONSELING KRISTEN DALAM PEMULIHAN ADIKSI NAPZA - Martha Luciana Abraham; Juliana Hindradjat (PT. Giat Konseling Nusantara, 2026)
Substance addiction is a multidimensional issue that not only damages physical and psychological well-being but also disrupts a person's identity, relationships, and spiritual life. From a Christian theological perspective, such damage reflects a distortion of the Imago Dei, the human vocation to mirror God’s character and will. This study aims to examine the restoration of the Imago Dei as a theological foundation for formulating a Christian counseling approach that can support holistic recovery from substance addiction. This research employs a qualitative approach through a literature study by reviewing theological works, Christian counseling literature, and studies related to addiction, which were then analyzed to identify principles relevant to identity and behavioral restoration. The findings indicate that recovery from addiction requires spiritual renewal and identity reconstruction through the work of Christ and intentional pastoral care. These insights suggest that Christian counseling grounded in the restoration of the Imago Dei may be oriented through spiritual assessment, spiritual reframing, emotional healing, behavioral transformation, relapse prevention, and supportive faith communities. This study concludes that the restoration of the Imago Dei provides a robust theological and practical framework for developing Christian counseling approaches that promote holistic human recovery, particularly in the areas of identity and spirituality.